Effects of an enzyme blend (livestock answer) in diets containing dried distillers grains with solubles on growth performance of nursery and finishing pigs - J M Benz; Jim L Nelssen; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
Two trials were conducted to determine the effects of an enzyme blend (Livestock Answer; Environmental Care and Share, Golden, CO) on growth performance of nursery and wean-to-finish pigs. Livestock Answer contains amylases, cellulases, proteases, lipases, and phytases. In Exp. 1, a total of 180 pigs (PIC TR4 × 1050, initially 12.3 lb and 21 d old) were used in a 28-d trial. Pigs were blocked by weight and allotted at weaning to 1 of 3 enzyme levels (0%, 0.125%, and 0.175%). There were 6 pigs per pen and 10 replications per treatment. Diets were corn-soybean meal based and contained 15% dried distillers grains with solubles (DDGS) during Phase 1 (d 0 to 14) and 25% DDGS during Phase 2 (d 14 to 28). From d 0 to 14, increasing enzyme level improved ADG (quadratic; P = 0.04) and F/G (linear; P = 0.05) and tended to improve (P<0.07) ADFI and pig weight on d 14. From d 14 to 28, enzyme level had no effect (P>0.20) on ADG or ADFI but worsened F/G (quadratic; P = 0.04). Pigs fed an enzyme blend for the first 14 d after weaning had improved growth performance. However, over the entire 28-d nursery period, enzyme level had no effect (P>0.22) on pig performance. In Exp. 2, a total of 224 nursery pigs (PIC TR4 ×1050, initially 13.4 lb and 21 d of age) were blocked by weight and allotted to 1 of 4 treatments. There were 8 pigs per pen and 7 pens per treatment. Livestock Answer was added at 0.125% to either the nursery or finisher stage or both in a 2 × 2 factorial arrangement (with and without in nursery and with and without in finisher). Diets were corn-soybean meal based and contained 15% DDGS from d 0 to 14, 25% DDGS from d 14 to 35, and 30% DDGS from d 35 to d 126. On d 126, pigs were harvested and carcass data were collected. Adding the enzyme to nursery, finishing, and nursery and finishing combined diets containing DDGS did not influence (P>0.20) ADG, ADFI, F/G, or any of the carcass criteria measured in Exp 2.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Swine; Dried distillers grains with solubles; Enzyme